2021
DOI: 10.1016/j.mayocpiqo.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Correlates in Patients With Takotsubo Syndrome During the COVID-19 Pandemic

Abstract: We completed a systematic review of published Takotsubo syndrome (TTS) cases during COVID-19 pandemic and performed clustering and feature importance analysis, and statistical testing for independence on the demographic, clinical and imaging parameters. Compared with the data before the COVID-19 pandemic, TTS was increasingly diagnosed in physical stress (mostly COVID-19 pneumonia)-triggered male patients without psychiatric/neurologic disorders, warranting further investigation to establish new reference crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(26 reference statements)
0
11
1
2
Order By: Relevance
“…Additionally, a systematic review of 123 patients with TTS during the COVID‐19 pandemic showed an in‐hospital morality rate of 23.3% which was significantly different by sex (38.7% in males and 13.9% in females; p = 0.03). 91 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a systematic review of 123 patients with TTS during the COVID‐19 pandemic showed an in‐hospital morality rate of 23.3% which was significantly different by sex (38.7% in males and 13.9% in females; p = 0.03). 91 …”
Section: Discussionmentioning
confidence: 99%
“…These differences could be due to including a higher number of cases in our systematic review and also differences in the number of patients with different past medical history and the medications used by them. Additionally, a systematic review of 123 patients with TTS during the COVID‐19 pandemic showed an in‐hospital morality rate of 23.3% which was significantly different by sex (38.7% in males and 13.9% in females; p = 0.03) 91 …”
Section: Discussionmentioning
confidence: 99%
“…Such specialists could also take part in prospective, coordinated multicenter studies of this rare, still nebulous pathology. Especially given the probability that new genetic mutations of coronaviruses or other organisms will eventually cause future pandemics, we must better prepare for the possibility that a substantial complication such as TTC will reappear ( 62 ). Whether or not within the context of COVID-19 or some future viral pandemic, the real incidence and pathophysiological mechanisms of TTC must be understood, and rational, effective approaches to treatment must be developed.…”
Section: Conclusive Commentsmentioning
confidence: 99%
“…No entanto, durante a pandemia, a STT foi cada vez mais relatada em indivíduos do sexo masculino, desencadeada por estresse físico (principalmente pneumonia por COVID-19) sem distúrbios psiquiátricos/neurológicos. Ademais, as características de imagem atípicas da STT foram frequentemente identificadas em ecocardiogramas transtorácicos à beira do leito (Chang et al, 2021).…”
Section: Epidemiologiaunclassified
“…A infecção por COVID-19 estava presente em 66,7% dos pacientes e gatilhos emocionais, distúrbios psiquiátricos e distúrbios neurológicos foram relatados em 33,3%, 12,1% e 6,1% dos pacientes, respectivamente. Além disso, Chang et al (2021) observaram que a mortalidade hospitalar de pacientes com COVID-19 e STT é superior do que sua mortalidade pré-pandemia. Esse estudo também demonstrou que pacientes do sexo masculino com STT tiveram mortalidade hospitalar quase 2,8 vezes maior em comparação com pacientes do sexo feminino.…”
Section: Epidemiologiaunclassified